Стратегии перевода и государственный контроль = Translation Strategies and State Control - Pild, Lea (Acta Slavica Estonica, 2017)
Acta Slavica Estonica is an international series of publications on current issues of Russian and other Slavic languages, literatures and cultures. This volume consists of two sections and includes articles by participants of two international scientific seminars: "Translation strategies and state control" (Tartu, December 8-10, 2016) and "Textbook as an ideological text" (Tartu, September 29-30, 2017). The focus of the book is on the relationship between government institutions and members of the translation community during the Soviet period; ideology and poetics of translations of works of art included in the Russian-Soviet literary canon; mechanisms of transmission of ideology in Russian imperial and Soviet school textbooks.